Identifying clinically meaningful benchmarks for gait improvement after total hip arthroplasty. Issue 1 (6th August 2015) - Foucher, Kharma C.
ABSTRACT: There are no established benchmarks for gait mechanics after total hip arthroplasty (THA). This study sought to identify minimum clinically important postoperative (MCIP) or minimum clinically important improvement (MCII) values for self‐selected walking speed, sagittal plane dynamic hip range of motion (HROM) (peak flexion‐peak extension) and peak hip adduction moments measured during quantitative gait analysis. Preoperative and 1‐year postoperative data collected during quantitative gait analysis, along with Harris Hip Scores (HHS), for 145 subjects were collected from a motion analysis data repository. The MCIP (or MCII) was defined as the 75th percentile mark on a plot of the cumulative percent of subjects with HHS ≥ 80 versus the postoperative value (or change) in the respective variable. 95% confidence intervals (CI) were calculated. Logistic regression was used to test the association of age, sex, BMI, and preoperative HHS with benchmarks. The MCIP of speed was 1.34 m/s (95%CI 1.30, 1.37); MCII was 0.32 (0.30, 0.35) m/s. The HROM MCIP was 30.0° (29.4°, 30.7°); MCII was 13.3° (12.1°, 14.8°). The adduction moment MCIP was 4.2% Body Weight × Height (4.0, 4.4); MCII was 0.87 (0.57, 1.17) % Body Weight × Height. Women were more likely to achieve MCII for HROM and MCIP for adduction moment (ORs 2.4–11.6, p  ≤ 0.031). Lower BMI predicted HROM and adduction moment MCIPs (ORs 0.85–0.88, p  ≤ 0.015). Lower preoperative HHS predicted speed, HROM and adduction moment MCIIs (ORs 0.95–0.97, p  ≤ 0.012). With further validation, clinically‐relevant gait benchmarks can enhance efforts to improve THA outcomes. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:88–96, 2016.